Investigating the sustainability of careers in academic primary care: a UK survey - Calitri, R; Adams, A; Atherton, H; Reeve, J; Hill, N (BioMed Central, 2014)
Background: The UK National Health Service (NHS) is undergoing institutional reorganisation due to the Health and Social Care Act-2012 with a continued restriction on funding within the NHS and clinically focused academic institutions. The UK Society for Academic Primary Care (SAPC) is examining the sustainability of academic primary care careers within this climate and preliminary qualitative work has highlighted individual and organisational barriers. This study seeks to quantify the current situation for academics within primary care. Methods: A survey of academic primary care staff was undertaken. Fifty-three academic primary care departments were selected. Members were invited to complete a survey which contained questions about an individual’s career, clarity of career pathways, organisational culture, and general experience of working within the area. Data were analysed descriptively with cross-tabulations between survey responses and career position (early, mid-level, senior), disciplinary background (medical, scientist), and gender. Pearson chi-square test was used to determine likelihood that any observed difference between the sets arose by chance. Results: Responses were received from 217 people. Career pathways were unclear for the majority of people (64%) and 43% of the workforce felt that the next step in their career was unclear. This was higher in women (52% vs. men 25%; χ2(3) = 14.76; p = 0.002) and higher in those in early career (50% vs. senior career, 25%) and mid-career(45%; vs. senior career; χ2(6) = 29.19, p < 0.001). The workforce appeared geographically static but unstable with only 50% of people having their contract renewed or extended. The majority of people (59%) have never been promoted by their institution. There were perceptions of gender equality even in the context of females being underrepresented in senior positions (19% vs. males 39%; χ2(3) = 8.43, p = 0.015). Despite these findings, the majority of the workforce reported positive organisational and cultural experiences. Conclusions: Sustainability of a academic primary care career is undermined by unclear pathways and a lack of promotion. If the discipline is to thrive, there is a need to support early and mid-career individuals via greater transparency of career pathways. Despite these findings staff remained positive about their careers.